(untitled) (Journal of actual problems of jurisprudence, 2018)
The Antique Law Culture and question about spiritual and semantic roots of the imperishable value of ancient law are the general and final subject of this publication. Therefore, the article is devoted to a number of fundamental concepts that characterize the deep meaning of Law in the context of intellectual, spiritual and rhetorical practice of Ancient Greek and Roman philosophy and jurisprudence. The special attention is paid to the «word of Law» and the «word about Law», which has made it possible to combine the philosophical and rhetorical aspects of the analysis of the Ancient Law Culture, and, in particular, to conclude that Aristotle’s rhetoric was the methodology of juridical discourse in the period of its becoming. Key words: spirit, idea, metaphor, law, rhetoric, word, philosophy.